2014
DOI: 10.1073/pnas.1413376111
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements activate endocytosis in plant cells

Abstract: It has long been observed that rare earth elements (REEs) regulate multiple facets of plant growth and development. However, the underlying mechanisms remain largely unclear. Here, using electron microscopic autoradiography, we show the life cycle of a light REE (lanthanum) and a heavy REE (terbium) in horseradish leaf cells. Our data indicate that REEs were first anchored on the plasma membrane in the form of nanoscale particles, and then entered the cells by endocytosis. Consistently, REEs activated endocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 37 publications
5
62
0
3
Order By: Relevance
“…It has been observed that La activates endocytosis in plant cells, and this process might play a role in La-mediated plant growth and development (Wang et al , 2014). We therefore investigated the effect of La on endocytosis in Arabidopsis roots.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been observed that La activates endocytosis in plant cells, and this process might play a role in La-mediated plant growth and development (Wang et al , 2014). We therefore investigated the effect of La on endocytosis in Arabidopsis roots.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1970s, REEs, particularly lanthanum (La), have been widely used in agriculture as plant growth stimulants because they promote crop growth (Hu et al , 2004; Feng et al , 2013). Indeed, REEs protect plants against certain plant diseases and stress conditions (Wang et al , 2014). A low concentration of La 3+ relieves plant growth inhibition, improves leaf water potential and water content, and increases soluble protein and proline contents while decreasing malondialdehyde contents under osmotic or salt stress (Feng et al , 1999; Xu et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations